Strategies to Improve Bamboo Craftsmen's Participation in Village Educational Tourism Development During the Pre-Launch Phase: A Case Study of Empowerment Policy in Mekarsari Village - Ajie Nugraha; Mulyaningsih; Luqman Nulmunir; Gugun Geusan Akbar (Jurnal Dialektika: Jurnal Ilmu Sosial, 2026)
Village educational tourism is frequently framed through Community-Based Tourism (CBT), yet many initiatives stall in the pre-launch phase when local actors are unprepared. This study examines Awi Edu-tourism in Mekarsari Village, Garut Regency, to identify barriers to bamboo craftsmen’s participation and to formulate empowerment strategies. Guided by community participation theory, self-efficacy, and empowerment, the research used a qualitative case-study design with semi-structured interviews, participant observation, and document analysis, followed by reflexive thematic analysis. Results show three interlinked constraints: limited understanding of edu-tourism beyond ‘produce-and-sell’ routines, low confidence to interact with visitors, and weak value awareness that craft knowledge can become an educational attraction. These conditions keep participation at an informational level rather than a substantive role in planning. Recommendations emphasise iterative concept workshops, scenario-based communication practice, and institutionalised artisan involvement in village forums with incentives. Findings contribute a pre-launch readiness map linking meaning, confidence, and institutional support to sustainable CBT. Keywords: Community Based Tourism, Edu-Tourism, Pre-Launch Readiness.